DIY Cultures and Underground Music Scenes - Bennett, Andy; Guerra, Paula; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
This volume examines the global influence and impact of DIY cultural practice as this informs the production, performance and consumption of underground music in different parts of the world. The book brings together a series of original studies of DIY musical activities in Europe, North and South America, Asia and Oceania. The chapters combine insights from established academic writers with the work of younger scholars, some of whom are directly engaged in contemporary underground music scenes. The book begins by revisiting and re-evaluating key themes and issues that have been used in studying the cultural meaning of alternative and underground music scenes, notably aspects of space, place and identity and the political economy of DIY cultural practice. The book then explores how the DIY cultural practices that characterize alternative and underground music scenes have been impacted and influenced by technological change, notably the emergence of digital media. Finally, in acknowledging theover 40-year history of DIY cultural practice in punk and post-punk contexts, the book considers how DIY cultures have become embedded in cultural memory and the emotional geographies of place. Through combining high-quality data and fresh conceptual insights in the context of an international body of work spanning the disciplines of popular-music studies, cultural and media studies, and sociology the book offers a series of innovative new directions in the study of DIY cultures and underground/alternative music scenes. This volume will be of particular interest to undergraduate students in the above-mentioned fields of study, as well as an invaluable resource for established academics and researchers working in these and related fields.
Introduction -- Andy Bennett and Paul Guerra -- -- Part I: Underground Music Scenes between the Local and the Translocal -- 1. Rethinking DIY Culture in a Post-Industrial and Global Context -- Andy Bennett and Paula Guerra -- 2. Visibility and Conviviality in Music Scenes -- Will Straw -- 3. Punk Stories -- Carles Feixa -- 4. Between Popular and Underground Culture: An Analysis of Bucharest Urban Culture -- Anda Georgiana Becu -- 5. The DIY as a Constitutive Resource of the Specific Punk Capital in France -- Pierig Humeau -- 6. Boys in Black, Girls in Punk: Gender Performances in the Goth and Hardcore Punk Scenes in Northern Germany -- Yvonne Niekrenz -- -- Part II: Music and DIY Cultures: DIY or Die! -- 7. Music, Protest Politics, DIY and Identity in the Basque Country -- Ion Andoni de Amo Castro -- 8. Home Economics: Fusing Imaginaries in the Musical Underground of Wellington, New Zealand -- Katie Rochow -- 9. Proud Amateurs: Deterritorialized Expertise in Contemporary Finnish DIY Micro-Labels -- Juho T. Kaitajrvi-Tiekso -- 10. Noise Records as Noise Culture: DIY Practices, Aesthetics and Trades -- Sarah Benham -- 11. Punk Positif: The DIY Ethic and the Politics of Value in the Indonesian Hardcore Punk Scene -- Sean Martin-Iveson -- -- Part III: Art, Music and Technological Change -- 12. So Far, Yet So Near: The Brazilian DIY Politics of Sofar Sounds A Collaborative Network for Live Music Audiences -- Jeder Silveira Janotti Jr and Victor de Almeida Nobre Pires -- 13. Cassette Cultures in Berlin: Resurgence, DIY Freedom or Sellout? -- Benjamin Dster and Raphal Nowak -- 14. Here Today: The Role of Ephemera in Clarifying Underground Culture -- John Willsteed -- 15. Birth of an Underground Music Scene? Creative Networks and (Digital) DIY Technologies in a Hungarian Context -- Emlia Barna -- -- Part IV: Music Scenes, Memory and Emotional Geographies -- 16. The Inoperative Subculture: History, Identity and Avant-Gardism in Garage Rock -- Daniel S. Traber -- 17. Collectivity and Individuality in US Free Folk Musics -- Maximilan Spiegel -- 18. The Independent Record Label, Ideology and Longevity: Twenty Years of Chemikal Underground Records in Glasgow -- J. Mark Percival -- 19. Verbal Sound System (199798): Recalling a Ravers DIY Practices in the British Free Party Counterculture -- Zoe Armour -- 20. A Howl of the Estranged: Post-Punk and Contemporary Underground Scenes in Bulgarian Popular Music -- Asya Draganova and Shane Blackman.
Also available in print format.
Keywords: Punk rock music -- Social aspects; Punk culture; SOCIAL SCIENCE / Sociology / General; Electronic books